Analisis Kepuasan Penumpang terhadap Kualitas Pelayanan Maskapai Garuda Indonesia di Bandar Udara Internasional Yogyakarta - Elang Panca (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Customer satisfaction is one of the targets that must be met by a company, especially a company engaged in services, how to get satisfaction customer is to improve the quality of service. This study aims to determine passenger satisfaction with the service quality of the Garuda Indonesia airline and the service quality attributes that can be developed by the Garuda Indonesia airline at Yogyakarta International Airport. This study uses a quantitative research design with a sample of Garuda Indonesia airline passengers. The data source sample was selected using purposive sampling which is included in non-probability sampling. The researcher used a questionnaire for the research instrument and required a sample of 100 respondents. The results of data collection will be processed using SPSS to obtain results. The results showed that, Garuda Indonesia airline passengers at Yogyakarta International Airport were satisfied with the quality of service provided by the airline, but there were still gaps based on the results of the gap analysis in the service quality of Garuda Indonesia Airlines at Yogyakarta International Airport was negative ( -), i.e. -0, 11, it shows that the services provided by Garuda Indonesia Airlines at Yogyakarta International Airport have not fully met customer expectations, the attributes contained in quadrant A are considered very important by passengers but the quality of service provided is not appropriate, namely on the Empathy Dimension, the 21st attribute Garuda Indonesia should prioritize the best interests of passengers. Keywords: performance, check-in counter officers, passenger satisfaction, Garuda Indonesia